Angiotensin II, a Neuropeptide at the Frontier between Endocrinology and Neuroscience: Is There a Link between the Angiotensin II Type 2 Receptor and Alzheimer’s Disease? - Gallo-Payet, Nicole; Guimond, Marie-Odile; Bilodeau, Lyne; Wallinder, Charlotta; Alterman, Mathias; Hallberg, Anders (Frontiers in Endocrinology, 2011)
Amyloid-β peptide deposition, abnormal hyperphosphorylation of tau, as well as inflammation and vascular damage, are associated with the development of Alzheimer’s disease. Angiotensin II (Ang II) is a peripheral hormone, as well as a neuropeptide, which binds two major receptors, namely the Ang II type-1 receptor (AT1R) and the type-2 receptor (AT2R). Activation of the AT2R counteracts most of the AT1R-mediated actions, promoting vasodilation, decreasing the expression of pro-inflammatory cytokines, both in the brain and in the cardiovascular system. There is evidence that treatment with AT1R blockers (ARBs) attenuates learning and memory deficits. Studies suggest that the therapeutic effects of ARBs may reflect this unopposed activation of the AT2R in addition to the inhibition of the AT1R. Within the context of Alzheimer’s disease (AD), modulation of AT2R signaling could improve cognitive performance not only through its action on blood flow/brain microcirculation but also through more specific effects on neurons. This review summarizes the current state of knowledge and potential therapeutic relevance of central actions of this enigmatic receptor. In particular, we highlight the possibility that selective AT2R activation by nonpeptide and highly selective agonists, acting on neuronal plasticity, could represent new pharmacological tools that may help improve impaired cognitive performance in Alzheimer’s disease and other neurological cognitive disorders.